Study on the use of mobile devices in schools: the case of Romania - Petronia Moraru; Gabriela Marchitan; Petrică Moraru; Carmen Hîrnea; Maria Ungureanu (Revista de Estudios e Investigación en Psicología y Educación, 2017)
The current dynamics of society is relevant also for the educational systems. The integration of mobile devices in education, as a bridge between inside and outside educational activities, is not fully exploited.  This paper will present a brief study regarding the mobile devices and ICT in Romanian educational system, and an analysis about teachers' skills and disponibility, to move to the next step of mobile-integrated educational system, the gap between the potential of the method BYOD/the schools' mobile devices, the practice of teaching using them, and the needs of students for their skills development, regarding of long life learning.